Using local radio stations and sports awareness - Taibi, Ammar; Kadri, hadj (sports creativity, 2025)
The media are important tools that strive for development and positive change. Therefore, most societies give them the importance they deserve. Among these media is radio, which is no less important than other media such as television, print media, and the internet, due to its many distinctive characteristics. These include the ease of acquiring receivers and its accessibility to listeners wherever they are. This has led it to strive to spread awareness and various values, whether social, political, or even sporting. Sporting is considered a cultural and social phenomenon linked to reality. It is a cultural requirement for everyone, reflecting a developed society and providing a broad field for communication within the community. When we look at sporting, we find ourselves facing a type of physical exercise or bodily movement that a person performs in response to a vital drive. However, it is performed automatically due to a psychological and vital foundation that embodies the essence and spirit of sporting. This is what has made it a social force and a cultural system, and what has endowed it with the components of a social order. Its success or failure depends on the readiness of the society that contains it. Sport has become part of culture, and sporting life part of cultural life. Physical activity has become essential for mental, intellectual, educational, and cultural development. Furthermore, sporting culture is considered an integral part of any true culture. Human beings, as an integrated whole, are the focus of culture; therefore, any definition of culture does not necessarily refer to the physical aspect, which is often neglected and deficient. Louis Awad wrote in this regard, saying, "Sport is part of the foundations of culture and civilization, but on the condition that young people are not exploited for political purposes, and on the condition that it does not turn into a kind of worship of the body and an affront to reason."